AB0811 Atherosclerosis assessment in systemic sclerosis patients without cardiovascular risk factors. (23rd January 2014) - Rosales Alexander, J.L.; Joven, B.; Salvatierra, J.; Cantero Hinojosa, J.; Carreira, P.E.
Abstract : Background: Atherosclerosis is an inflammatory disease with increased prevalence in connective tissue disorders, including systemic sclerosis (SSc), that might contribute to the excess mortality present in this disease. Recent studies have found that mean carotid intima media thickness (IMT) and number of carotid plaques, measured by ultrasonography (US) are significantly higher in SSc patients compared to healthy controls. These findings suggest that SSc patients may have increased cardiovascular (CV) risk. Objectives: To assess early atherosclerosis using carotid US in SSc patients without classic CV risk factors compared to healthy controls, and to analyze the factors associated with higher IMT values in SSc patients Methods: Patients with SSc, fulfilling the 1980 ACR SSc criteria or the proposed 2001criteria for early SSc, were prospectively included in a database created in 1989 at the "Doce de Octubre" hospital, containing demographic and clinical information. For the study, 54 living Spanish patients without classic CV risk factors were selected, and matched according to sex and age with 54 healthy controls. CV risk was assessed using the SCORE chart calibrated for Spain (S-SCORE). The presence of plaques and common carotid artery (CCA) IMT were evaluated by B doppler US. Chi-square or Fisher's tests were used to assess differences between qualitative variables and Student's t test for comparing means. Factors associated with higher IMT values were analyzed by multivariate lineal regression analysis. Results: Most SSc patients (94%) were women, 61% had limited cutaneous involvement. Mean age was 58±13 years and mean disease duration was 14±10 years. Mean S-SCORE was 0.68±1.04 in SSc patients and 0.83±1.19 in controls, NS. In SSc low CV risk was found in 33(61%) patients and intermediate risk in 21(39%). In controls low CV risk was found in 30 (56%) patients and intermediate risk in 24 (44%), NS. In CCA US, plaques were found in 7 (13%) SSc patients and 2 (3.7%) controls, p=0.08. Mean IMT was 0.67±0.17 mm in SSc patients and 0.59±0.72 mm in controls, (p<0.001). In SSc patients, higher IMT values were associated with older age (p=0.03), higher systolic blood pressure (p=0.04) and longer disease duration (p=0.03). Conclusions: Our study suggest that CV risk assessment in SSc patients should include carotid US to measure IMT and evaluate the presence of plaques, since the SCORE chart seems to underestimate the CV risk in this population. Further prospective studies are needed to correctly define the value of carotid US in SSc patients. References: Au K, Singh MK, Bodukam V, Bae S, Maranian P, Ogawa R, Spiegel B, McMahon M, Hahn B and Khanna D. Atherosclerosis in Systemic Sclerosis. A Systematic Revie and Meta-Analysis. Arthritis & Rheumatism. Vol 63 No 7, July 2011, pp 2078-90. Hettema ME, Zhang D, Leeuw K, Stienstra Y, Smit AJ, Kallenberg CGM and Bootsma H. Early atherosclerosis in systemic sclerosis and its relation to disease or tradional risk factors. Arthritis Research and Therapy 2008, 10: R49. Disclosure of Interest: None Declared